A Theory of Dynamic Oligopoly, I: Overview and Quantity Competition with Large Fixed Costs - Maskin, Eric; Tirole, Jean (Econometrica, 1988)
The authors introduce a class of alternating-move, infinite-horizon models of duopoly. The timing captures the presence of short-run commitment s. They apply this framework to a natural monopoly in which costs are so large that at most one firm can make a profit. The firms install short-run capacity. In the unique symmetric Markov perfect equilibriu m, only one firm is active and practices the quantity analogue of lim it pricing. For commitments of brief duration, the market is almost c ontestable. The authors conclude with a discussion of more general mo dels where the alternating timing is derived rather than imposed. Copyright 1988 by The Econometric Society.